2016
DOI: 10.18632/oncotarget.14059
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine 5′-monophosphate blocks acetaminophen toxicity by increasing ubiquitination-mediated ASK1 degradation

Abstract: Acetaminophen (APAP) overdose is the most frequent cause of drug-induced liver failure in the world. Hepatic c-jun NH2-terminal protein kinase (JNK) activation is thought to be a consequence of oxidative stress produced during APAP metabolism. Activation of JNK signals causes hepatocellular damage with necrotic and apoptotic cell death. Here we found that APAP caused a feedback increase in plasma adenosine 5′-monophsphate (5′-AMP). We demonstrated that co-administration of APAP and 5′-AMP significantly amelior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In addition, we measured the activation of c-Fos, reported as downstream of JNK signaling pathway (Yang et al, 2016b). Acetaminophen caused a marked increase on c-Fos activation, but SP600125 did not inhibit the activation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we measured the activation of c-Fos, reported as downstream of JNK signaling pathway (Yang et al, 2016b). Acetaminophen caused a marked increase on c-Fos activation, but SP600125 did not inhibit the activation.…”
Section: Discussionmentioning
confidence: 99%
“…However, PRMT5 does the methylation of R89 in ASK1 and promotes the interaction between ASK1 and Akt, thus advancing S83 phosphorylation and ASK1 negative regulation [226] . Moreover, in a study, it has been reported that 5′-AMP administration weakens ASK1 methylation and enhances ubiquitination, which therefore prompts ASK1 degradation, inferring that ASK1 methylation could add to its stability [227] .…”
Section: Post-translational Modifications (Ptms) For Ask1 Regulationmentioning
confidence: 99%